Assessment of Fulvic Acid-Like Fractions during Tannery Waste Composting. Issue 3 (2nd July 2016) - Benlboukht, Fatima; El Fels, Loubna; Bouamri, Rachid; Amir, Soumia; Hafidi, Mohamed
Abstract: Changes in the structural composition of fulvic acids were followed during composting of tannery solid waste after neutralization of its acidity by ammonium or by lime. Different techniques (elemental analysis, Fourier transform infrared (FTIR), 13 C-NMR spectroscopy) were applied. During both trials of composting, a decrease of carbon and increase of oxygen occurred, which originated from strong microbial oxidation and preservation of some structures during composting. In fact, Nuclear Magnetic Resonance (NMR) spectra showed the preservation of anomeric or tannin structures around 105 ppm. The infrared (IR) spectral data showed a decrease in the intensity of COO − group bands (1623 and 1399.5 cm −1 ); this is correlated with a decrease of fulvic acid levels. The variations observed in NMR spectra could be explained by the involvement of COO − groups of certain structures in polycondensing to form humic acids. The fulvic acids remain composed of less polycondensed structures with a –COOH extremity, as supported by a decrease of the C/H ratio. In contrast, in the trial with addition of ammonia a slight increase in N content occurred, a decrease in absorbance in the 1730–1000 cm −1 regions compared to the absorbance around 3400 cm −1, and a strong decrease of carboxyl carbon in the 13 C-NMR spectra.